Tumor Necrosis Factor Alpha Signaling and Organogenesis - You, Kai; Gu, Hui; Yuan, Zhengwei; Xu, Xuewen (Frontiers in Cell and Developmental Biology, 2021)
Tumor necrosis factor alpha (TNF-α) plays important roles in processes such as immunomodulation, fever, inflammatory response, inhibition of tumor formation, and inhibition of viral replication. TNF-α and its receptors are ubiquitously expressed in developing organs and they regulate the survival, proliferation, and apoptosis of embryonic stem cells (ESCs) and progenitor cells. TNF-α is an important inflammatory factor that also regulates the inflammatory response during organogenesis, and its cytotoxic effects can interfere with normal developmental processes, even leading to the onset of diseases. This review summarizes the various roles of TNF-α in organogenesis in terms of its secreting pattern, concentration-dependent activities, and interactions with other signaling pathways. We also explored new potential functions of TNF-α.